Hipersuperfícies Estáveis CMC com Fronteira Livre numa Bola Euclidiana - Zulema Katherine Gutierrez Ttamina (2018)
In this work, we will study the result obtained by Ezequiel Barbosa which states that if B is a ball in a Euclidean space (...), with dimension (...), then the stable CMC hypersurface free boundary (...) suit (...), where L denotes the border length of , A denotes the area of ?? and H denotes the mean curvature of . Consequently, if the border is dipped, then is fully geodesic, or starred with respect to the center of the ball. This result is an improvement of a Theorem shown by Ros and Vergasta in [4].